2022
DOI: 10.3389/fcvm.2021.808071
|View full text |Cite
|
Sign up to set email alerts
|

Risk Prediction Model for Uncontrolled Hypertension in Chinese Community

Abstract: BackgroundUncontrolled hypertension rate was still high across China. This study develops and validates an index to help quantify the combination of socio-behavioral aspects to screen high-risk patients in uncontrolled hypertension in Chinese primary care.MethodsA cross-sectional study included 1,039 of patients with hypertension in the Chinese community. We assessed independent risk factors of uncontrolled blood pressure (defined as having a blood pressure ≥140/90 mmHg, even with antihypertensive therapy) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The smoking as a main focus that perceived needs education and health counseling to stop smoking [9]. The research in China identified that the worker elders, uninsured, unmarried and social-behavior aspects as the independent predictors of uncontrolled blood pressure among hypertensive elders [10].…”
Section: Introductionmentioning
confidence: 99%
“…The smoking as a main focus that perceived needs education and health counseling to stop smoking [9]. The research in China identified that the worker elders, uninsured, unmarried and social-behavior aspects as the independent predictors of uncontrolled blood pressure among hypertensive elders [10].…”
Section: Introductionmentioning
confidence: 99%